Inhibition of namnam (Cynometra cauliflora L.) leaves extract on the growth of Porphyromonas gingivalis - Ulpiyah, Zakiyya; Shita, Amandia Dewi Permana; Wahyukundari, Melok Aris (Padjadjaran Journal of Dentistry, 2019)
Introduction: Porphyromonas gingivalis growth should be prevented to minimise inflammation in periodontal tissues. Antibacterial herbs need to be considered because there are side effects caused by synthetic antibacterial drugs. Namnam (Cynometra cauliflora L.) leaves are known for having antibacterial effects. The purpose of this research was analysing the inhibition potential, and the highest inhibition concentration of namnam leaves extract on the growth of Porphyromonas gingivalis. Methods: 24 samples were divided into 6 groups. The positive control group was given 0.2% chlorhexidine, and the treatment group was given various concentrations (100%, 80%, 60%, 40%, and 20%) of namnam leaves extract. The disc which spilled by various concentrations of namnam leaves extracts and 0.2% chlorhexidine was placed on a medium which has been inoculated by P. gingivalis, then incubated at 37ºC for 48 hours. The inhibition zone was measured using a vernier calliper. Results: The concentration of 100% had the highest average inhibition zone value, which was 11.43 mm. The content in namnam leaves extracts which serve as antibacterial were tannins, flavonoids, triterpenoids, saponins and quinones. Conclusion: Namnam leaves extract can inhibit the growth of P. gingivalis. 100% of namnam leaves extract has the highest antibacterial inhibition zone.Keywords: Antibacterial, Namnam leaves extract, periodontal disease, Porphyromonas gingivalis